Pengaruh Inflasi Dan BI Rate Terhadap Harga Saham Perusahaan LQ45 Pada Bursa Efek Indonesia - Risa Ratna Gumilang; Dikdik Nadiansyah (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
This research is motivated by a mismatch between theories regarding stock price movements that are influenced by inflation rates and BI Rate with conditions that occur in the field. In theory, when stock prices increase, it will be influenced by falling inflation and the BI Rate, and vice versa. But this is different from the conditions that occur in the field. This research aims to examine and determine the effect of inflation and BI Rate on the LQ45 company stock prices. This study uses the quantitative method by using the secondary data. From the results of the study using the t test, inflation has a tcount 0.828 and a Sig. 0.417. This shows that partially, inflation does not have a significant effect on stock prices. While the BI Rate has a value of -2.511 and a Sig. 0.020. This shows that partially, the BI Rate has a significant effect on stock prices. In correlation, inflation has a Sign value. (2-tailed) 0.068. This shows that in correlation, inflation does not have a significant relationship to the BI Rate. Simultaneously (F test), inflation and the BI Rate have a Fcount value of 5.005 and a Sig. (2-tailed) of 0.017. This shows that simultaneously, inflation and the BI Rate have a significant effect on stock prices.